Impaired Autonomic Responses to Emotional Stimuli in Autoimmune Limbic Encephalitis - Schröder, Olga; Schriewer, Elisabeth; Golombeck, Kristin S.; Kürten, Julia; Lohmann, Hubertus; Schwindt, Wolfram; Wiendl, Heinz; Bruchmann, Maximilian; Melzer, Nico; Straube, Thomas (Frontiers in Neurology, 2015)
Limbic encephalitis (LE) is an autoimmune-mediated disorder that affects structures of the limbic system, in particular the amygdala. The amygdala constitutes a brain area substantial for processing of emotional, especially fear-related signals. The amygdala is also involved in neuroendocrine and autonomic functions, including skin conductance responses (SCRs) to emotionally arousing stimuli. This study investigates behavioral and autonomic responses to discrete emotion-evoking and neutral film clips in a patient suffering from LE associated with contactin-associated protein-2 (CASPR2)-antibodies as compared to a healthy control group. Results show a lack of SCRs in the patient while watching the film clips, with significant differences compared to healthy controls in the case of fear-inducing videos. There was no comparable impairment in behavioral data (emotion report, valence and arousal ratings). The results point to a defective modulation of sympathetic responses during emotional stimulation in patients with LE, probably due to impaired functioning of the amygdala.